Wearable resistance sprint running is superior to training with no load for retaining performance in pre-season training for rugby athletes - Neil Bezodis (European Journal of Sport Science, 2020)
This study determined the effects of a six-week lower-limb wearable resistance training (WRT) intervention on sprint running time, velocity, and horizontal force-velocity mechanical variables. Twenty-two collegiate/semi-professional rugby athletes completed pre- and post-intervention testing of three maximal effort 30 m sprints. A radar device was used to measure sprint running velocity from which horizontal force-velocity mechanical profiling variables were calculated. All athletes completed two dedicated sprint training sessions a week for six-weeks during pre-season. The intervention (wearable resistance, WR) group completed the sessions with 1% body mass load attached to the left and right shanks (i.e. 0.50% body mass load on each limb), whilst the control group completed the same sessions unloaded. For the control group, all variables were found to detrain significantly (p ≤ 0.05) over the training period with large detraining effects (ES > 0.80) for theoretical maximal horizontal force, slope of the force-velocity profile, maximal ratio of force, index of force application, 5 m and 10 m times. For the WR group, there were no significant changes to any recorded variables (all p > 0.05) and all effects of training were trivial or small (ES < 0.50). After adjustment for baseline differences, significant between group differences were found for all variables (large effects, ES > 0.80) except theoretical maximal velocity, 30 m time, and maximal velocity. The addition of light wearable resistance to sprint training during a six-week pre-season block enables the maintenance of sprint performance and mechanical output qualities that otherwise would detrain due to inadequate training frequencies.